2015
DOI: 10.1108/amhid-02-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Does supported living work for people with severe intellectual disabilities?

Abstract: Purpose – The purpose of this paper is to look at whether a move to a supported living model of care from traditional residential group homes could improve the quality of life for those with a severe intellectual disability and other challenging needs. Design/methodology/approach – Six men with severe intellectual disabilities moved from two residential homes into new-build individual flats. Their quality of life was measured using a bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 6 publications
2
25
0
2
Order By: Relevance
“…As per the exclusion criteria, all studies reported on participants between 18-65 years, with most reporting on a population with a mean age of approximately 40 years. Most studies reported on samples that consisted of over 50% males [40,42,43,[45][46][47][48]53,57,[59][60][61] and two studies reported on a sample that was 100% male [49,50]. The number of participants included in the studies ranged from 6 to 8,892 people.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…As per the exclusion criteria, all studies reported on participants between 18-65 years, with most reporting on a population with a mean age of approximately 40 years. Most studies reported on samples that consisted of over 50% males [40,42,43,[45][46][47][48]53,57,[59][60][61] and two studies reported on a sample that was 100% male [49,50]. The number of participants included in the studies ranged from 6 to 8,892 people.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…However, results of Emerson et al [42] may be influenced by a cohort effect as participants included people who had experienced institutional living. In regards to emotional functioning, Marlow and Walker [49] found that people's mood increased one month after they moved from group homes into individualized flats and that these changes were maintained after six months. Valk-Kleibeuker et al [59] found that mood did not change for participants in their study until 18 months post traumatic brain injury (TBI), after which it significantly improved.…”
Section: Body Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Les deux autres études de cette catégorie sont associées au modèle environnemental. Elles mesurent le niveau de qualité de vie des personnes présentant une DI en fonction de leur type d'hébergement dans la communauté (Bertelli et al, 2013;Marlow et Walker, 2015).…”
Section: Méthodeunclassified